The Effect of School Culture of Certified Teacher Educators and Principal Academic Supervision on Pedagogical Competence - Effendi, Sofyan; Prihatin, Yoga; Nasukha, Muntoha (South Asian Journal of Social Sciences and Humanities, 2025)
The quality of education at the school level (learning) is influenced by the pedagogical competence of teachers in carrying out their duties, so the pedagogical competence of teachers is one of the important factors in achieving educational success. In accordance with Government Regulation No. 74 of 2008 concerning teachers, it is stated that pedagogical competence is the ability of teachers in managing student learning, which includes a deep understanding of educational foundations. This not only improves the quality of education but also contributes to achieving greater educational goals in society. The ability to understand students is not just about knowing their academic abilities, but also includes the emotional, social, and cultural aspects that shape their learning experiences. The purpose of this research is to: 1) determine the influence of school culture of certified educator teachers on pedagogical competence, 2) determine the influence of academic supervision by the principal on pedagogical competence, 3) determine the influence of school culture of certified educator teachers and academic supervision by the principal on pedagogical competence. The pedagogical competence of certified educators in Tegal Regency has several issues, including some teachers who do not yet understand assessment and lack time discipline, suboptimal teaching preparation, unoptimized learning preparation, inadequate classroom management, and the need for teachers to improve varied teaching strategies to create an enjoyable and memorable learning atmosphere for students. This research uses a quantitative method. The data collection technique uses a questionnaire as the research instrument. The research location is at SMK Bhakti Praja, Tegal Regency. The sample in this study consisted of 60 certified educators. The results of this study indicate that 10.7% of teachers’ pedagogical competence is influenced by school culture, 10% is influenced by the academic supervision of the principal, and 17% is influenced by both school culture and the academic supervision of the principal simultaneously. The findings of this study show that: 1) School culture partially affects pedagogical competence, 2) The academic supervision of the principal partially affects pedagogical competence, 3) School culture and academic supervision simultaneously affect pedagogical competence.